2013
DOI: 10.1007/s11552-013-9503-z
|View full text |Cite
|
Sign up to set email alerts
|

Tennessee Emergency Hand Care Distributions and Disparities: Emergent Hand Care Disparities

Abstract: Background Hand trauma is the most frequently treated injury in emergency departments, but presently there is a crisis of insufficient emergency coverage. This study evaluates the discrepancy of emergent and elective hand care trends based on socioeconomic factors in the state of Tennessee. Methods We identified 119 hospitals in Tennessee that contained operating and emergency room facilities. Of these, 111 hospitals participated in a survey to determine the availability of elective and emergency hand surgery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…This finding is consistent with previous work that found that poor counties in Tennessee are underserved by hand surgeons. 7 It has also been demonstrated in other health care systems: in Germany, every percentage change in the prevalence of people with comprehensive health insurance is associated with a 2.1 percent increase in hospital specialist density. 15 Furthermore, it is likely that this pattern contributes to the difficulties some hospitals face in accessing specialist hand services.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This finding is consistent with previous work that found that poor counties in Tennessee are underserved by hand surgeons. 7 It has also been demonstrated in other health care systems: in Germany, every percentage change in the prevalence of people with comprehensive health insurance is associated with a 2.1 percent increase in hospital specialist density. 15 Furthermore, it is likely that this pattern contributes to the difficulties some hospitals face in accessing specialist hand services.…”
Section: Discussionmentioning
confidence: 90%
“…Other contributory factors may include physician preference for elective ambulatory care without on-call responsibility 6 and socioeconomic incentives. 7 Financial incentives might play a role in surgeon density, and government payers are likely a significant contributor in low-socioeconomicstatus states. Further studies should consider subspecialist hand surgeon income in well-served and underserved states to determine whether this is a factor driving distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey in 2010 determined that 51% of emergency departments (EDs) reported inadequate orthopedic coverage, while 80% reported inadequate hand surgery coverage specifically. 3,4 With the shortage of hand surgeons to evaluate and treat the existing volume of traumatic hand injuries, telemedicine in this subspecialty has been suggested as a possible adjunct in care and a useful solution. 5,6 There is an estimated incidence of 1130 upper extremity injuries per 100 000 persons per year, but in some instances with limited access or lack of access to a specialty provider for consultation.…”
Section: Introductionmentioning
confidence: 99%
“…There is a known lack of emergency hand services in the US [8]. Counties that are medically underserved and with low income tend to have difficulty finding emergency hand coverage [1]. Surgical specialists have been steadily dropping their hand call privileges due to financial pressures, medico-legal risk, specialty competence, and time requirements [4].…”
Section: Discussionmentioning
confidence: 99%